Review of solar photovoltaic water pumping system technology for irrigation and community drinking water supplies. (September 2015) - Chandel, S.S.; Nagaraju Naik, M.; Chandel, Rahul
Abstract: The deficit in electricity and high diesel costs affects the pumping requirements of community water supplies and irrigation; so using solar energy for water pumping is a promising alternative to conventional electricity and diesel based pumping systems. Solar water pumping is based on photovoltaic (PV) technology that converts solar energy into electrical energy to run a DC or AC motor based water pump. The main objective of the study is to present a comprehensive literature review of solar pumping technology, evaluate the economic viability, identify research gaps and impediments in the widespread propagation of solar water pumping systems and technology. The study focuses on update on solar water pumping technology, performance analysis, optimum sizing, degradation of PV generator supplying power to pump, economic and environmental aspects and advances in PV materials and efficiency improvements. An update on the current state of research and utilization of solar water pumping technology is presented. Factors affecting performance of PV water pumping system, degradation of PV modules and efficiency improving techniques of PV water pumping systems are identified. Solar water pumping is found to be economically viable in comparison to electricity or diesel based systems for irrigation and water supplies in rural, urban and remote regions. The investment payback for some PV water pumping systems is found to be 4–6 years. The recent Indian incentives for PV pumping and policy initiatives for the promotion of solar water pumping in developing countries are also discussed. Potential follow-up research areas are also identified.